2005
DOI: 10.1097/01.prs.0000148373.86487.04
|View full text |Cite
|
Sign up to set email alerts
|

Bone Quality and Healing in a Swine Vascularized Bone Allotransplantation Model Using Cyclosporine-Based Immunosuppression Therapy

Abstract: Although vascularized bone and joint allotransplantation is a promising new treatment option for reconstructing large bone defects, the need for immunosuppressive agents to prevent rejection in these procedures poses a major problem. This problem stems from the fact that several of these agents can cause harmful side effects, such as alterations in bone quality and healing. Therefore, the purpose of this study was to determine what effect the commonly used immunosuppressant regimen cyclosporine A-based combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…With axial compression testing, we found the elastic modulus to be less than normal bone at 16 weeks. Vossen et al demonstrated a similar finding at 12 weeks after bone VCA, although direct comparison with our study is not possible due to differences in methodology . Interestingly, on the microscale the allotransplant elastic modulus and hardness proved not to be significantly different than contralateral tibias.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…With axial compression testing, we found the elastic modulus to be less than normal bone at 16 weeks. Vossen et al demonstrated a similar finding at 12 weeks after bone VCA, although direct comparison with our study is not possible due to differences in methodology . Interestingly, on the microscale the allotransplant elastic modulus and hardness proved not to be significantly different than contralateral tibias.…”
Section: Discussionsupporting
confidence: 58%
“…As both blood type and the major histocompatibility haplotypes (the swine leucocyte antigen or SLA complex) have been well defined, the mini pig is proving of value for study of many VCA tissues . A limitation of the swine model is its rapid growth .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported previously in rodent and porcine models of long-bone allotransplantation using tacrolimus immunosuppression. 28,29,31,63 Our findings additionally support reconstructive clinical applications of isolated vascularized bone allografts using a potentially limited course of tacrolimus immunosuppression. 41 The dose and duration of tacrolimus therapy to achieve stable bony union is unknown, as is whether bone quality could be maintained in the absence of immunosuppression in our model.…”
Section: Discussionsupporting
confidence: 70%
“…[60][61][62] Indeed, similar studies of vascularized long-bone transplantation in large-animal models have found that prednisone administration impaired bone healing/bone quality, and may have been responsible for immunosuppression-related complications leading to animal loss. 29,31 In contrast, tacrolimus-based therapy, whether alone or in combination with CD28 costimulatory blockade, provided adequate immunosuppression to prolong vascularized bone allograft survival without impaired physiologic healing in our model. Similar results have been reported previously in rodent and porcine models of long-bone allotransplantation using tacrolimus immunosuppression.…”
Section: Discussionmentioning
confidence: 85%